2016
DOI: 10.7567/jjap.55.067001
|View full text |Cite
|
Sign up to set email alerts
|

Sensor chip design for increasing surface-plasmon-assisted fluorescence enhancement of the V-trench biosensor

Abstract: A sensor chip design for the V-trench biosensor, which is an instrument for highly sensitive fluorescence assay, was investigated to increase its sensitivity. A simulation based on the transfer matrix method revealed that the vertex angle and electric field enhancements of the V-trench biosensor chip are increased by employing a high-refractive-index material for the chip. It was proved that a chip made of high-refractive-index glass for press molding exhibited a 1.4-fold larger electric field enhancement than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The sensor is equipped with a V-shaped microfluidic channel, which functions as a prism to excite the SPR, and it can perform sensitive biosensing based on SPRF. SPR-induced fluorescence emission on the V-trench was confirmed for fluorescent molecules and quantum dot fluorescent labels in previous studies [ 19 , 20 , 21 ]. Herein, the evaluation of a CNT fluorescent label using a V-trench biosensor designed for CNTs is presented.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…The sensor is equipped with a V-shaped microfluidic channel, which functions as a prism to excite the SPR, and it can perform sensitive biosensing based on SPRF. SPR-induced fluorescence emission on the V-trench was confirmed for fluorescent molecules and quantum dot fluorescent labels in previous studies [ 19 , 20 , 21 ]. Herein, the evaluation of a CNT fluorescent label using a V-trench biosensor designed for CNTs is presented.…”
Section: Introductionsupporting
confidence: 69%
“…In this study, the performance of CNTs as a fluorescent label for target analyte detection using SPRF was evaluated. A V-trench biosensor, which was developed as a miniature and simple SPRF apparatus [ 19 , 20 , 21 ], was used for the evaluation. The sensor is equipped with a V-shaped microfluidic channel, which functions as a prism to excite the SPR, and it can perform sensitive biosensing based on SPRF.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is of interest to know details of the molecular structure of the applied SAM, the supplier gave no information concerning this matter. It has to be noted that this type of SAM is assigned especially for biotin–streptavidin assays and was already used . The deposition of the SAM terminated with biotin, followed by streptavidin, and biotinylated horseradish peroxidase onto the sensor surface shows impressively that the biomolecule stack only binds to the gold electrode and not to the PPy:PSS electrode (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Although BSA with ≈66 kDa is a large molecule compared with biotin (≈244 Da) and streptavidin (≈52 kDa), control experiments revealed that subsequently applied proteins are not hindered when binding to the biotin of the SAM. Kazuma et al pointed out that BSA does not bind to the SAM itself by means of localized surface plasmon resonance [17b]. Omitting the SAM in the MTP experiments led to absorption values in the photometric measurements of 0.19 without BSA blocking and 0.02 with blocking, respectively.…”
Section: Discussionmentioning
confidence: 99%